PERHITUNGAN KLAIM JAMINAN HARI TUA PADA BPJS DALAM PERSPEKTIF AKAD KAFALAH - Aulil Amri; Nurma Yunita (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
The Old Age Guarantee Program (JHT) is one of the BPJS programs. JHT has a benefit value that can be claimed by former employees. In practice, the calculation of JHT claims must be in accordance with the BPJS policy. When viewed from Islamic law, the guarantee is called kafalah. However, in the kafalah contract, the calculation of JHT claims and the value of the benefits has gaps that are not in accordance with Islamic law. This thesis is focused on answering three important things, 1) How is the calculation on the BPJS policy regarding JHT for PT IMARA employees. 2) What are the benefits received by former employees of PT IMARA on JHT claims. 3) What is the perspective of the kafalah contract on the calculation of claims and the value of JHT benefits for employees at BPJS PT IMARA. This research is a qualitative research that is descriptive analysis with a sociological normative approach, where the data obtained comes from observations and interviews. The results of the study show that, first, the calculation of old age security claims is a combination of the basic salary and fixed allowances reported by PT IMARA to BPJS Ketenagakerjaan. The amount of JHT contributions for participants receiving wages is 5.7% of income, with details of 3.7% being borne by the company and 2% being borne by the employee himself which is deducted from the salary. Second, the benefits of JHT are in the form of cash, the amount of which is the accumulated value of the contributions plus the results of the development. Third, the calculation of JHT claims and JHT benefits in the perspective of the kafalah contract that is applied to PT IMARA when viewed from the pillars of kafalah is in accordance with the Shari'a. However, under the terms of the kafalah contract, this is contrary to the Shari'a because the contributions of BPJS participants are developed by placing them in several portfolios, including conventional bank deposits or bonds based on interest loans. In the development of claims there is also a 5% interest where the interest follows the BI Rate system.